Reorganization of Hydration Water of DPPC Multilamellar Vesicles Induced by l -Cysteine Interaction - Arias, Juan Marcelo (2018)
The aim of this study is to analyze the consequences of water redistribution on the structure and stability of phospholipid bilayers induced by cysteine (Cys). This interaction is studied with 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) multilamellar vesicles in gel (30 °C) and liquid crystalline (50 °C) state; experimental studies were performed by means of Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, and differential scanning calorimetry (DSC). The polar head sites of the lipid molecules to which water can bind are identified by competition with compounds that form hydrogen bonds, such as Cys. FTIR spectroscopy results revealed that there is a Cys interaction with the phospholipid head groups in the gel and liquid crystalline phases. Raman spectra were measured in the gel state. They were dominated by vibrations of the fatty acyl chains, with superposition of a few bands from the head group, and clearly showed that the S-H stretching band of Cys shifted to lower frequencies with a decrease in its force constant. DSC disclosed an overview of the behavior of the multilamellar vesicles in the working temperature range (30-50 °C) and showed how the increase of the molar ratios modified the environment of the polar head and the hydrocarbon chains. A loss of the pretransition (TP) and an increase in the temperature of main transition (Tm) with increasing Cys/DPPC molar ratio were observed.